Molecular Cloning and Characterization of a meta/para-O-Methyltransferase from Lycoris aurea - Sun, Bin (Int J Mol Sci, 2018)
O-methyltransferases (OMTs) have been demonstrated to play key roles in the biosynthesis of plant secondary metabolites, such as alkaloids, isoprenoids, and phenolic compounds. Here, we isolated and characterized an OMT gene from Lycoris aurea (namely LaOMT1), based on our previous transcriptome sequencing data. Sequence alignment and phylogenetic analysis showed that LaOMT1 belongs to the class I OMT, and shares high identity to other known plant OMTs. Also, LaOMT1 is highly identical in its amino acid sequence to NpN4OMT, a norbelladine 4′-OMT from Narcissus sp. aff. pseudonarcissus involved in the biosynthesis of Amaryllidaceae alkaloids. Biochemical analysis indicated that the recombinant LaOMT1 displayed both para and meta O-methylation activities with caffeic acid and 3,4-dihydroxybenzaldehyde, and showed a strong preference for the meta position. Besides, LaOMT1 also catalyzes the O-methylation of norbelladine to form 4′-O-methylnorbelladine, which has been demonstrated to be a universal precursor of all the primary Amaryllidaceae alkaloid skeletons. The results from quantitative real-time PCR assay indicated that LaOMT1 was ubiquitously expressed in different tissues of L. aurea, and its highest expression level was observed in the ovary. Meanwhile, the largest concentration of lycorine and galanthamine were found in the ovary, whereas the highest level of narciclasine was observed in the bulb. In addition, sodium chloride (NaCl), cold, polyethylene glycol (PEG), sodium nitroprusside (SNP), and methyl jasmonate (MeJA) treatments could significantly increase LaOMT1 transcripts, while abscisic acid (ABA) treatment dramatically decreased the expression level of LaOMT1. Subcellular localization showed that LaOMT1 is mainly localized in cytoplasm and endosome. Our results in this study indicate that LaOMT1 may play a multifunctional role, and lay the foundation for Amaryllidaceae alkaloid biosynthesis in L. aurea.